SysIoTML: uma técnica para modelagem de aplicações no contexto de IoT - SIQUEIRA, Rodrigo do Nascimento (2023)
The Internet of Things (IoT) is a concept that connects smart objects equipped with sensors, networks, and processing technologies that work together to provide an environment in which smart services are brought to users. Systems modeling should be conducted to create IoT Systems and ensure the implementation of a good system. IoT increases the complexity of systems modeling due to novel concepts that need to be addressed. However, there are no established techniques for systems modeling for this specific context. This paper presents the development of a new technique for IoT systems modeling, the SysIoTML, an extension of SysML. Such techniques consider specific aspects of IoT Systems (behavior and interactivity). We proposed the SysIoTML and conducted a concept-proof to analyze the technical feasibility. The developed technique proved useful, and the participants were able to model the proposed problem. The main contribution is to advance IS modeling through a new technique.